The Influence of Human Resources Competence and the workload on an employee's performance Through Organizational Commitment in the Employee Scope of the Parepare City Population Control and Family Planning Service - Magfirah Kadir; Haris Maupa; Muhammad Sobarsyah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2022)
This study aims to determine how much influence the relationship between human resource competence and workload has on employee performance through organizational commitment. This type of research is quantitative research. The sample in this study used a saturated sample, namely all employees of the Parepare City Population Control and Family Planning Service, totaling 94 people consisting of various positions and jobs within the agency. Data collection techniques using a questionnaire. The data is processed using SmartPLS 3. The data analysis technique used is path analysis. The results showed that HR competence and workload had a positive effect on organizational commitment and employee performance. The organizational commitment has no effect on employee performance and HR competence and workload has no effect on employee performance through an organizational commitment within the employee scope of the Parepare City Population and Family Planning Agency